Chemistry of clerodane diterpenes isolated from Dodonaea species in Western Australia - Moussa, Vasoulla Noelle (Curtin University, 2015)
A new clerodane diterpene was isolated from the leaf resin of Dodonaea ceratocarpa in an appreciable quantity. The inherent chemistry of this new compound was studied to evaluate its potential as a starting material for the pharmaceutical industry. A suite of new clerodanes were synthesised.Cordytropolone is a natural product isolated from Cordyceps that gave moderate inhibition against P. falciparum in vivo. A total synthesis was investigated using a thiophene-1,1-dioxide.